2019
DOI: 10.1002/mnfr.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated Fatty Acids in a High‐Fat Diet and Niacin Protect from White Fat Dysfunction in the Metabolic Syndrome

Abstract: Scope Obesity is a principal causative factor of metabolic syndrome. Niacin potently regulates lipid metabolism. Replacement of saturated fatty acids by MUFAs or inclusion of omega‐3 long‐chain PUFAs in the diet improves plasma lipid levels. However, the potential benefits of niacin in combination with MUFAs or omega‐3 long‐chain PUFAs against white adipose tissue (WAT) dysfunction in the high fat diet (HFD)‐induced metabolic syndrome are unknown. Methods and results Male Lepob/obLDLR−/− mice are fed a chow di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
2
12
0
Order By: Relevance
“…Building from previous research reporting that MUFAs in HFDs, in sharp contrast to SFAs, favor the homeostasis and a healthy expansion of eWAT in a mouse model of metabolic syndrome, [ 38 ] we now show that HFDs enriched in MUFAs or SFAs have distinct impacts within multilineage progeny of myeloid and lymphoid cells in a polygenic developmental model of HFD‐induced obesity. All HFDs tested induced weight gain, increased adiposity, promoted dyslipidemia, and led to dysregulation of key hub genes involved in inflammation and energy balance in eWAT.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Building from previous research reporting that MUFAs in HFDs, in sharp contrast to SFAs, favor the homeostasis and a healthy expansion of eWAT in a mouse model of metabolic syndrome, [ 38 ] we now show that HFDs enriched in MUFAs or SFAs have distinct impacts within multilineage progeny of myeloid and lymphoid cells in a polygenic developmental model of HFD‐induced obesity. All HFDs tested induced weight gain, increased adiposity, promoted dyslipidemia, and led to dysregulation of key hub genes involved in inflammation and energy balance in eWAT.…”
Section: Discussionsupporting
confidence: 63%
“…[ 50 ] It is conceivable that these observations may also result as a direct consequence of the inflammatory profile triggered by HFD‐SFAs on the mobilization of splenic lymphoid cells (mainly B cells) to adipose depots, which was a previously described mechanism of the adaptive response for reducing inflammation in the eWAT of obese mice. [ 15 ] This mechanism would not be relevant, despite the role of macrophages and particularly dendritic cells as potent antigen presenting cells in adipose tissue, [ 51 ] as it has been demonstrated that HFDs enriched in MUFAs promote a surrounding lipid environment dominated by oleic acid and the prevalence of alternatively activated macrophages in eWAT [ 38 ] and that triglyceride‐rich lipoproteins isolated from volunteers after the ingestion of a high‐fat meal rich in olive oil impede maturation and pro‐inflammatory activation of monocyte‐derived dendritic cells. [ 52 ] In fact, the repression of the Elane gene in the visceral adipose depot may suggest that HFDs enriched in MUFAs did not induce the recruitment of neutrophils into eWAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olive oil, the main dietary fat in the Mediterranean diet, due to its content of oleic acid (MUFA) and minor constituents, modulate different processes linked to chronic low-grade inflammation [ 24 ]. This view is in contrast to diets rich in SFAs, such as the “meat-based” or “Westernized” diets, which are inductive of inflammatory states [ 25 ]. One of the key processes of inflammation is the maturation and activation of circulating myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids present in olive oil are mostly mono- and polyunsaturated fatty acids, such as oleic (C18:1), linoleic (C18:2), and linolenic (C18:3) acids [48]. Although these fatty acids are known to have beneficial effects on health [47,49], there was no effect on the mitigation of 5-FU-induced hematological toxicity. From these observations, we perceived that the long-chain fatty acids present in PLAG were not key elements that exert therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%